ECOTOXICOLOGICAL ASSESSMENT LEAD CONTAMINATION IN SOIL SYSTEM AND VEGETATION NEAR REFUELLING STATIONS - Білик, Т. І.; Штика, О. С.; Падалка, А. О.; Цуркан, К. О. (Science-based technologies, 2009)
The problem of lead pollution of soil system and vegetation near refuelling stations is currently the object of considerable attention in present publication. Results of chemical analysis of soil samples and leaves taken on the teritory of refuelling stations are presented.